Association of MicroRNAs With Risk of Stroke: A Meta-Analysis - Deng, Yidong; Huang, Peijian; Zhang, Fan; Chen, Tao (Frontiers in Neurology, 2022)
Objectives: Altered expression of microRNAs (miRNAs) may contribute to disease vulnerability. Studies have reported the involvement of miRNA in the pathophysiology of ischemic stroke. Methods: We performed a meta-analysis of data from 6 studies that used a panel of miRNAs with altered expressions to diagnose ischemic stroke with the Bayesian framework. The I2 test and Cochran's Q-statistic were used to assess heterogeneity. Funnel plots were generated and publication bias was assessed using Begg and Egger tests. Results: On summary receiver operating characteristics (SROC) curve analysis, the pooled sensitivity and specificity of altered miRNA expressions for diagnosis of ischemic stroke was 0.92 (95% confidence interval [CI] 0.80–0.97) and 0.83 (95% CI 0.71–0.90), respectively; the diagnostic odds ratio was 54.35 (95% CI 20.39–144.92), and the area under the SROC curve was 0.93 (95% CI 0.90–0.95). Conclusions: Our results showed a link between dysregulation of miRNAs and the occurrence of ischemic stroke. Abnormal miRNA expression may be a potential biomarker for ischemic stroke.